Polyaniline@cellulose nanofibers multifunctional composite material for supercapacitors, electromagnetic interference shielding and sensing - Chuanyin Xiong; Congmin Zheng; Zhao Zhang; Qing Xiong; Qiusheng Zhou; Dongping Li; Mengxia Shen; Yonghao Ni (Journal of Materiomics)
Recently, multifunctional materials have received widespread attention from researchers. Cellulose nanofibers (CNF) is one of biomass materials with abundant hydroxyl groups, which shows great potential in manufacturing multifunctional composite material. In this paper, a kind of polyaniline@CNF/polyvinyl alcohol-H2SO4 multifunctional composite material (PANI@CNF/PVA-H2SO4) was successfully designed by in-situ chemical polymerization of conductive polyaniline (PANI) onto CNF aerogel with high aspect ratio, and then coated with PVA-H2SO4 gel. The composite material has a specific capacitance of 502.2 F/g at a scan rate of 5 mV/s as supercapacitor electrode. Furthermore, when the composite was assembled into a symmetrical supercapacitor, it can still provide an energy density of 11.49 W·h/kg at a high power density of 413.55 W/kg. Besides, the as-obtained PANI@CNF/PVA-H2SO4 composite has an excellent electromagnetic shielding performance of 34.75 dB in X-band. In addition, due to the excellent flexibility of CNF and PVA, the PANI@CNF/PVA-H2SO4 composites can be further applied to stress sensors to detect pressure and human motion signals.